Influencia de los factores de riesgo en la muerte fetal intermedia y tardía en el hospital II Essalud – Tarapoto período 1994 – 1998 estudio de casos y controles - Cáceres López, Elvira del Carmen (2000)
In order to tag influenced it in the chorosity of intermediate risk in 14 fetal death and late was carried out in the Hospital II ESSALUDT orapoto a study of cases and controls (observational, comparative and retrospective study). the study sample consisted of 70 cases of deaths and 70 of newborns alive (controls). Them data collected correspond to cases that occurred during the years 1994 to 1998, the same that were analyzed through the package statistical EPIINFO. After the respective analysis was reached the following conclusions: 1. the incidence of fetal death intermediate and late in the Hospital II ESSALUD-T arapoto during the years 1994 to 1998 is 21.66 X 1000 N.V. 2. The factors of risk that influence in it death fetal (P < 0.05) are: age maternal s 19 years and > of 35 years, level partner economic low, presence of toxemia, weight placental < of 300 gr., weight of the newly born < of 2500 gr., fo. ITA e ino.decuo.do control preno.to.I, edo.d...